Taxonomic studies in the genus Acrostemon Kl. and related genera - Oliver, E G H (Department of Biological Sciences, 2023)
Investigations were carried out on the genus Asrostemon Kl. in the Ericaceae. Examination of variation ranges in the species of Acrostem912 revealed that the two monotypic genera, Hexastemon Kl. and Arachnocalyx Compton, could not be upheld as separate genera. They were therefore reduced under Acrostemon. Studies of variation and intergradation in the distinguishing characters between Acrostemon and the genera, Simochocheilus Kl. and Syndesmanthus Kl., have shown that the three genera may have to be incorporated into a single genus in a future revision of the Ericaceae. However further study is necessary to clarify this problem. In this work eighteen taxa have been investigated and of these taxa only seven remained unaltered. In the genus Acrostemon thirteen species have been recognised, of which two are newly described, A. vernicosus and A. glutinosus. One new subspecies and two species reduced to varietal level have been recognised. been found necessary. Five changes in nomenclature have Two species have been referred to different genera, Blaeria concinna and Sim£cheilus fourcadei. Studies of the cytology of five species of Acrostemon indicate that the basic chromosome number for the genus is twelve.